Behavior of Estonian Oil Shale in Acidic Oxidative Conditions - Niidu, Allan; Grénman, Henrik; Muldma, Kati; Kaldas, Kristiina; Mikli, Valdek; Lopp, Margus (Frontiers in Chemical Engineering, 2022)
Oxidation of oil shale has been a long-sought alternative to classical thermal processing as a potential source of raw materials for the chemical industry. A number of different methods have been applied, but thus far the one of the most effective ways to transform the oil shale to value added products, e.g. aliphatic terminal dicarboxylic acids is oxidation with nitric acid. In order to have an insight into reactivity of oil shale in nitric acid a study focusing on the behaviour of oil shale particles was undertaken. To that end particle size distribution, surface area and carbon content is measured alongside the amount of total residual solids. Under acidic conditions all carbon measured by elemental analysis corresponds to organic carbon since inorganic carbon is present as carbonate in starting material. Thus, measuring carbon content in solid residue will give us an indirect efficiency indication of overall oxidation process. Results reveal that total solid residue amounts from 20% to 34% of initial value after 24 h of reaction, whilst total carbon content ranges from 4% to 14% from starting values. Therefore, in our case applied reaction conditions allow to extract around 90% of organic carbon from the solid phase.